2016
DOI: 10.1210/en.2016-1701
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Ablation of Progesterone Receptor Membrane Component 2 Causes Female Premature Reproductive Senescence

Abstract: The nonclassical progesterone receptors progesterone receptor membrane component (PGRMC) 1 and PGRMC2 have been implicated in regulating cell survival of endometrial and ovarian cells in vitro and are abundantly expressed in these cell types. The objective of this study was to determine if Pgrmc1 and Pgrmc2 are essential for normal female reproduction. To accomplish this objective, Pgrmc1 and/or Pgrmc2 floxed mice (Pgrmc2fl/fl and Pgrmc1/2fl/fl) were crossed with Pgr-cre mice, which resulted in the conditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 63 publications
1
23
0
4
Order By: Relevance
“…These PRs are composed of PR membrane component (PGRMC)-1 and PGRMC2, and the G-protein-coupled membrane PRs (56). Although a role for these receptors cannot be ruled out, a major role is not likely based on the PGRMC1-and PGRMC2-KO phenotypes reported in mice (57,58) and the finding that membrane PRs signal via Ga s and Ga i , not Ga q/11 (59). Despite these observations, further studies are required to understand whether these receptors play any role in the Ga q/11 -dependent acquisition of uterine receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…These PRs are composed of PR membrane component (PGRMC)-1 and PGRMC2, and the G-protein-coupled membrane PRs (56). Although a role for these receptors cannot be ruled out, a major role is not likely based on the PGRMC1-and PGRMC2-KO phenotypes reported in mice (57,58) and the finding that membrane PRs signal via Ga s and Ga i , not Ga q/11 (59). Despite these observations, further studies are required to understand whether these receptors play any role in the Ga q/11 -dependent acquisition of uterine receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…These concepts challenge previous notions on processes taking place during pregnancy and invite not only to revisit former data but also to advance in the research of these endocrine-immune mechanisms from this novel perspective. Of note, a number of technical 21Gr fl/fl (9, 10) -Pgrmc1 fl/fl and Pgrmc2 fl/fl (30) tools to discriminate the receptor-specific pathways are to date available ( Table 2) and promise exciting progress in the research in the field.…”
Section: Immune Pathways Mediated By Progesterone and Glucocorticoidsmentioning
confidence: 99%
“…In vitro studies with SIGCs and human granulosa/luteal cells have demonstrated that depletion of either PGRMC1 or PGRMC2 resulted in an inappropriate entry into the cell cycle, which often lead to granulosa cell apoptosis [5,7]. To determine if PGRMC1 could be depleted within the ovary, Pgrmc1/2 fl/fl mice [21] were mated to Amhr2-cre mice [17,22]. This breeding strategy resulted in a 73% reduction in ovarian Pgrmc1 mRNA compared to controls (n = 3/group; P = 0.02).…”
Section: Resultsmentioning
confidence: 99%